Effect of Different Depths of Planting and Manuring on the Growth and Survival of Poplars in Ravine Lands-II - Singh, Bakhshish; Monappa, K.; Mistri, M. S. (Indian Forester, 1969)
The effect of three depths of planting (D1-60 cm; D2-90 cm; D3-120 cm) and two levels of manuring (M0 no manuring, M1-manuring @ 5 kg F.Y.M. per pit) On height, diameter growth and survival percent of Populus casale 488 were reported earlier (1) on the basis of the studies conducted at the Central Soil Conservation Research Station, Vasad (Gujarat) during 1965-67. The results of some additional investigastions regarding the effect of various treatments and available soil moisture on the growth characteristics and water balance of the plants are reported in this paper. The studies reveal that deep planting gave significantly better height and diameter growth, leaf size, leaf moisture per cent, relative turgidity (of leaves), percentage of the plants with active growth in the later parts of the growth season, percentage of plants without any leaf fall at the end of winter, percentage of plants without any die back of their leading shoots in dry summer months and survival per cent of the plants at the end of two growth seasons as compared to the medium (D2) and shallow (D1) depths of planting. Manuring (M1) gave significantly better height and diameter growth, leaf size, relative turgidity and survival per cent than the un- manured plants (M0) but it (M1) had no significant effect on leaf moisture per cent. Un-manured plants (M0) had significantly higher saturation deficit in their leaves as compared to the manured plants (M1). Moreover, the shallow depth of planting (D1) gave significantly higher saturation deficit than the medium depth of planting (D2), which in turn gave significantly higher saturation deficit than deep planting (D3). The effect of deep planting in enhancing the growth and vigour of the plants was found mainly due to the increase in available soil moisture per cent with the increase in soil depth.